3D Printing of Multiscale Ti64‐Based Lattice Electrocatalysts for Robust Oxygen Evolution Reaction. Issue 24 (20th July 2022) - Guo, Binbin; Kang, Jiahui; Zeng, Tianbiao; Qu, Hongqiao; Yu, Shixiang; Deng, Hui; Bai, Jiaming
Abstract: Electrically assisted water splitting is an endurable strategy for hydrogen production, but the sluggish kinetics of oxygen evolution reaction (OER) extremely restrict the large‐scale production of hydrogen. Developing highly efficient and non‐precious catalytic materials is essential to accelerate the sluggish kinetics of OER. However, currently used catalyst supports, such as copper foam, suffer from inferior corrosion resistance and structural stability, resulting in the disabled functionality of 3D conductive networks. To this end, a novel 3D freestanding electrode with corrosion‐resistant and robust Ti–6Al–4V titanium alloy lattice as the catalyst support is designed via a 3D printing technology of selective laser melting. After the coating of core–shell Cu(OH)2@CoNi carbonate hydroxides (CoNiCH) on the designed lattice, a unique micro/nano‐sized hierarchical porous structure is formed, which endows the electrocatalyst with a promising electrocatalytic activity (a low overpotential of 355 mV at 30 mA cm −2 and Tafel slope of 125.3 mV dec −1 ). Computational results indicate that the CoNiCH exhibits optimized electron transfer and the catalytic activity of the Ni site is higher than that of the Co site in the CoNiCH. Therefore, the integration of robust catalyst supports and highly active materials opens up an avenue for reliable and high‐performance OER electrocatalysts. Abstract : A corrosion‐resistant and mechanically robust Ti–6Al–4V porous catalyst substrate is fabricated by selective laser melting 3D printing. After the coating of Cu(OH)2 @CoNi carbonate hydroxides, a multiscale porous structure is designed for promising electrocatalytic performance including electrochemical stability and mechanical stability. Density functional theory and density of state calculations reveal the catalytically active sites and optimized electron transfer of the electrocatalysts.